Epistemology of Bodies as Closets: Queer Theologies and the Resurrection of Martyrized Christo-Morphic Bodies - Aguilar Contreras, Mercy (Religions, 2024)
This article seeks to rethink martyrdom, suffering, and resurrection from the perspective of queer theologies within the Latin American context and in dialogue with the praxis of the first faith communities who witnessed Jesus’ martyrdom. Starting from the queer body of Jesus—which incorporates in its praxis an ethos without gender violence and discrimination—the theological reflection contributes to the recovery of the fundamental principles of human experience. To this end, the analysis begins by addressing the feminist contribution to the understanding of violence against women to then rethink the intersection of bodies, sexuality, and violence against queer individuals and communities as a theological locus. It concludes by recognizing that queer theologies configure a resistant theological community that empowers queer bodies as a territory of hope of resurrection and transformative political action that does not disregard the suffering and the injustices perpetrated against them.